Young Stalin - Sebag Montefiore, Simon 1965- (Alfred A. Knopf, 2007)
The shadowy journey from obscurity to power of the Georgian cobbler's son who became the Red Tsar--the man who, along with Hitler, remains the modern personification of evil: a merciless psychopath who was, as well, a consummate politician, the dynamic world statesman who helped create and industrialize the USSR, outplayed Churchill and Roosevelt, and defeated Hitler? Historian Montefiore tells the story of a charismatic, turbulent boy born into poverty, of doubtful parentage, scarred by his upbringing but possessed of unusual talents. Admired as a romantic poet and trained as a priest, he found his true mission as a fanatical revolutionary. A mastermind of bank robbery, protection rackets, arson, piracy and murder, he was equal parts terrorist, intellectual and brigand. The paranoid criminal underworld was Stalin's natural habitat, and murderous banditry and political gangsterism, combined with pitiless ideology, enabled Stalin to dominate the Kremlin--and create the USSR in his flawed image.